The Impact of Embracing New Antenatal Screening Guidelines on Complications Related to Grand Multiparity in a Jordanian Tertiary Referral Center - Fida Thekrallah; Nadia Muhaidat; Ayman Qatawneh; Kamil Fram; Naser Al-Husban; Fida Asali (Clinical and Experimental Obstetrics & Gynecology)
Background: Universal screening, including thyroid dysfunction, gestational diabetes, and performing morphology and growth scans, was introduced in the healthcare system to improve perinatal care and pregnancy outcomes. Pregnancy-related complications are usually higher in grand multiparous women and their advanced maternal age. This study aimed to compare the impact of implementing a universal screening strategy protocol versus the selective screening for grand multiparous pregnant women aged ≥35 years on the incidence of adverse pregnancy outcomes and the associated risk factors. Methods: A retrospective cohort study of two groups (n = 89/group) of healthy grand multiparous women aged ≥35 years and who either delivered between 2011–2012 and underwent selective screening, or between 2016–2017 and were universally screened, was conducted at the Department of Obstetrics and Gynecology, Jordan University Hospital. Results: The universal screening protocol detected more cases of women with gestational diabetes, gestational hypertension, and polyhydramnios 7, 4, and 9 more times, respectively, than the selective screening procedure. However, the results of universal screening tests for thyroid function and glucose tolerance were abnormal in only a small number of women. Furthermore, the cesarean section rate was reduced from 45% in the selective screening group to 1% in the universal screening group. No other significant differences in pregnancy or neonatal complications between the two groups were noted. Conclusions: Implementing new perinatal care protocols, including universal screening for thyroid disease and gestational diabetes, morphological and growth scans significantly decreased the rate of cesarean section in grand multiparous women with advanced maternal age, but did not affect pregnancy or neonatal complications. However, larger studies are needed to obtain more representative results among women in high-risk group for gestational diabetes mellitus (GDM) and thyroid dysfunction.